2021
DOI: 10.5802/alco.169
|View full text |Cite
|
Sign up to set email alerts
|

The Erdős–Ko–Rado theorem for 2-intersecting families of perfect matchings

Abstract: A perfect matching in the complete graph on 2k vertices is a set of edges such that no two edges have a vertex in common and every vertex is covered exactly once. Two perfect matchings are said to be t-intersecting if they have at least t edges in common. The main result in this paper is an extension of the famous Erdős-Ko-Rado (EKR) theorem [4] to 2-intersecting families of perfect matchings for all values of k. Specifically, for k 3 a set of 2-intersecting perfect matchings in K 2k of maximum size has (2k − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A c c e p t e d m a n u s c r i p t It is known that if a group has a regular subgroup, then there is a weighting of the conjugacy classes so that the ratio bound holds with equality [15,Theorem 3.5]. It would be interesting to know of more cases where it can be shown that such a weighting exists.…”
Section: Further Workmentioning
confidence: 99%
“…A c c e p t e d m a n u s c r i p t It is known that if a group has a regular subgroup, then there is a weighting of the conjugacy classes so that the ratio bound holds with equality [15,Theorem 3.5]. It would be interesting to know of more cases where it can be shown that such a weighting exists.…”
Section: Further Workmentioning
confidence: 99%
“…This result has motivated consideration of "intersecting" families of many A c c e p t e d m a n u s c r i p t other combinatorial objects using diverse proof techniques and has developed into an active and broad area of research. There are many recent results giving analogs of the EKR theorem; see, for example, [9,13,16,20,26] or [12] and the references within. In this work, we prove an extension of the EKR theorem to systems of uniform set partitions.…”
Section: Introductionmentioning
confidence: 99%